STUDI KASUS IMBANGAN ANGKUTAN SEDIMEN DI KALI KRASAK - Lanaria Pangestu, Darmono (Universitas Negeri Yogyakarta, 2014)
This study aims to find out the volume of a flood plan and balance between sediment raised inthe mining of sand and sediment that comes in the time of flooding in kali Krasak river’s arearegional of Kuwu’an.The method of study is using observation method, interview method, andliterature method. Hydrology data used in this study is map kali Putih river, map rain stasiun,and gradation of sand grains. To calculate the volume of a flood plan is using the rationalmethod, weduwen method, and hasper method. And to calculate sediment transport usingMayer, Peter and Muller formulation.The calculation based on four rains station Kalibawang,Kemput, Plunyon, Babadan station using (1) Rasional, (2) Weduwen and (3) Hasper to fiveyears reissue period are (1) 418,68 m3/second, (2) 145,08 m3/second and (3) 58,90 m3/second.The result of the calculation of sediment transport using Meyer, Petter and Muller formulationproduces sediment transport base for the entire widht of the river of 4,16 m3/second, and basesediment transport for one hour of 14.962 m3. The study result show that the mining sediment ofKuwu’an area is 172.800 m3/year. So the mining was done in Kuwu’an for one year is 172.800m3 can be offset by during floods for 11,54 hours resulting heaps of 172.823 m3.Keywords: Balance river Krasak, flood plan, sediment transport